The Elusive Legal Definition of Terrorism at the United Nations: An Inhibition to the Criminal Justice Paradigm at the State Level? (Strathmore Law Journal, 2017)
Terrorism is indisputably a serious security threat to states and individuals. Yet, by the end of 2016, there was still lack of consensus on the legal definition of terrorism at the United Nations (UN) level. The key organs of the UN, the Security Council (UNSC) and the General Assembly (UNGA), are yet to agree on a legal definition of terrorism. This disconnect is attributed partly to the heterogeneous nature of terrorist activities and ideological differences among member states. At the UN level, acts of terrorism are mainly tackled from the angle of threats to international peace and security. In contrast, at the state level, acts of terrorism are largely defined as crimes and hence dealt with from the criminal justice paradigm. This article argues that the lack of a concrete legal definition of terrorism at the UN level undermines the holistic use of the criminal justice paradigm to counter-terrorism at the state level. To effectively counter-terrorism the UNSC and the UNGA have to agree on a legal definition of terrorism in their resolutions. This will streamline efforts to combat terrorism at the state level and consolidate counter-terrorism measures at the international level. The draft comprehensive Convention on Measures to Eliminate Terrorism (the Draft Convention) should be tailored to fill gaps and provide for a progressive legal definition of acts of terrorism.